(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background Intravenous anaesthetic agents are used commonly to induce anaesthesia, as induction is usually smoother and more rapid than that associated with most of the inhalation agents. Thiopentone is the most widely used intravenous induction agent in current anaesthetic practice. Propofol (2,6 diisopropyl phenol) is a new rapidly acting intravenous anaesthetic. The rapid redistribution and metabolism of propofol, result in a short elimination half life. Midazolam is an imidazobenzodiazepine with relatively rapid onset of action and high metabolic clearance compared to other benzodiazepine. Objectives This prospective study was carried out to compare the induction characteristics of thiopentone, midazolam and propofol in elderly patients. Methods Ninety adult patients, aged between 60-80 years with ASA grade I &II who were scheduled for general surgery in Bangabandhu Sheikh Mujib Medical University, CMH Dhaka and CMH Saidpur were included in this study. The patients were divided into three groups of thirty each according to a randomization table.The overall performance of the drugs were assessed by recording the following parameters: 1) Pain on injection. 2) Induction time ( The time from start of injection to the loss of eye lash reflex). 3) Coughing 4. Involuntary motor activity. 5. Apnoea (present/absent). 6. Haemodynamic changes (Heart rate and blood pressure at 2 min before injection, after induction and 1min, 3min and 5min after intubation). 7. Recovery time ( From the end of reversal until the patient responded to vocal command(eye opening, tongue protrution). Results The incidence of pain on injection was greater in propofol group(38%), which was statistically significant(p<0.01). The induction time was significantly longer(p<0.001) in the midazolam group. Incidence of excitatory effects was more common in propofol group(p<0.05). Incidence of apnoeic episodes were significantly greater in thiopentone and propofol group than midazolam group(p<0.05). Propofol caused significant decrease in systolic, diastolic and mean arterial pressure at 3 & 5 minutes after intubation(p<0.001).Neither Thiopentone, midazolam nor propofol caused significant change in heart rate. Recovery time in midazolam group was significantly longer(p<0.001). Conclusion Thiopentone is the drug of choice for induction in elderly patients because of rapid induction, recovery and the least effect on arterial pressure. Propofol has no clear advantage over thiopentone and has the additional problem of a significant decrease in blood pressure. Midazolam, although safe, is clearly not the ideal drug for induction in elderly patients because of slow onset of action and delayed recovery. DOI: http://dx.doi.org/10.3329/jbsa.v26i1.19808 Journal of Bangladesh Society of Anaesthesiologists 2013; 26(1): 5-11